Case report: Combination therapy of envafolimab with endostar for advanced non-small cell lung cancer with low PD-L1 expression - Wu, Shuo; Dong, Changhong; Hu, Chenxi (Frontiers in Oncology, 2024)
In the management of advanced non-squamous non-small cell lung cancer (NSCLC) without driver gene mutations, the current therapeutic strategies encompass chemotherapy, chemotherapy combined with anti-angiogenic therapy, and chemotherapy combined with immunotherapy. For patients with high programmed death-ligand 1(PD-L1) expression, monotherapy with immune checkpoint inhibitors is a viable option. Recognizing that some patients cannot tolerate or decline chemotherapy, clinical practice has introduced non-chemotherapeutic treatment regimens, which have shown promising results. This article presents a clinical case of advanced NSCLC with low PD-L1 expression and negative driver gene mutations. The patient was treated with a chemotherapy-free regimen combining envafolimab with endostar. After 17 months of follow-up, both the primary tumor and metastatic lesions exhibited significant reduction, and no notable adverse reactions were observed. This case demonstrates the efficacy of envafolimab combined with endostar in the treatment of advanced NSCLC. This regimen enhances treatment safety and patient compliance, potentially offering a novel therapeutic option for patients with advanced NSCLC characterized by low PD-L1 expression and negative driver gene mutations.